Analisis Pengaruh Kepemimpinan dan Tanggung Jawab Agama dalam Menanggapi Tantangan Organisasi: Studi Kasus pada Kepemimpinan IPPNU - Elfi Haniatul Mafiroh; Wahyu Eko Pujianto (Jurnal Pengabdian Kepada Masyarakat, 2023)
This research explores the impact of religious leadership and responsibility in an organizational context, with a focus on the role of the Chair of the IPPNU. The research method involves interviews with sources to understand how to overcome organizational problems before aeend during leadership. The results of the interview highlight participatory strategies in problem solving and wise evaluation after holding the position of chairman. The resource person emphasized the importance of effective time allocation to manage responsibilities amidst busy schedules, by prioritizing what needs to come first.Furthermore, this research describes the real practice of the IPPNU Chair in proving religious responsibility. Prioritizing religious aspects, such as prioritizing prayers before events, becomes concrete actions that support organizational values. These findings provide an understanding of how religious values ​​can be manifested in real daily actions and contribute to strong leadership.In conclusion, this research details the significant role of leadership and religious values ​​in managing an organization like IPPNU. The implications of these findings can help develop better leadership strategies and strengthen the quality of religious organizations to face internal and external dynamics.